2019
DOI: 10.3389/fpls.2019.00341
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic and Environmental Assessment of a Polyculture Rooftop Soilless Urban Home Garden in a Mediterranean City

Abstract: Urban planning has been focusing its attention on urban rooftop agriculture as an innovative way to produce local and reliable food in unused spaces in cities. However, there is a lack of quantitative data on soilless urban home gardens and their contribution to self-sufficiency. The aim of the present study is to provide quantitative agronomic and environmental data on an actual soilless urban garden to estimate its degree of self-sufficiency and sustainability. For this purpose, an 18 m 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 22 publications
2
26
0
4
Order By: Relevance
“…For example, Sanyé-Mengual et al (2015b) assessed the performance of a rooftop home garden in Bologna (Italy), concluding that year-round polyculture, i.e., growing a wide variety of vegetables, meets the residents' demand for diversified foods. Similarly, Boneta et al (2019) found that 8.2 m 2 of rooftop polyculture can cover up to 62% of the average vegetable consumption per capita in the region of Catalonia. In addition to Boneta et al (2019), Orsini et al (2014) described the existence of large variations in the yields throughout the year when producing food in urban rooftops, as well as the difficulties found in producing vegetables in cold periods.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…For example, Sanyé-Mengual et al (2015b) assessed the performance of a rooftop home garden in Bologna (Italy), concluding that year-round polyculture, i.e., growing a wide variety of vegetables, meets the residents' demand for diversified foods. Similarly, Boneta et al (2019) found that 8.2 m 2 of rooftop polyculture can cover up to 62% of the average vegetable consumption per capita in the region of Catalonia. In addition to Boneta et al (2019), Orsini et al (2014) described the existence of large variations in the yields throughout the year when producing food in urban rooftops, as well as the difficulties found in producing vegetables in cold periods.…”
Section: Introductionmentioning
confidence: 90%
“…Similarly, Boneta et al (2019) found that 8.2 m 2 of rooftop polyculture can cover up to 62% of the average vegetable consumption per capita in the region of Catalonia. In addition to Boneta et al (2019), Orsini et al (2014) described the existence of large variations in the yields throughout the year when producing food in urban rooftops, as well as the difficulties found in producing vegetables in cold periods.…”
Section: Introductionmentioning
confidence: 90%
“…Catalogna Verde). Hydroponic production in perlite grow bags was selected as the control system as it is a standard system for horticultural production in the Mediterranean region, and this system can be used in both commercial and small-scale urban growing contexts [30,39,81].…”
Section: Novel Sustainable Growing Media Alternativesmentioning
confidence: 99%
“…Agronomy 2020, 10, x FOR PEER REVIEW 4 of 28 scale urban growing contexts [30,39,81]. These media were also tested on their ability to mitigate stress in lettuce crops during an induced drought period, in order to understand their potential to reduce irrigation requirements and buffer shocks in the hydroponic system.…”
Section: Growing Media Preparationmentioning
confidence: 99%
“…However, UA is not free of environmental impacts. Similar to conventional agricultural systems, nutrient discharge resulting from intensive fertilizer use is particularly problematic due its impact on water eutrophication ( Muñoz et al, 2008 ; Torrellas et al, 2012 ; Romero-Gámez et al, 2014 , 2012 ; Boneta et al, 2019 ). The application of circular economy strategies in UA systems could help mitigate these impacts.…”
Section: Introductionmentioning
confidence: 99%